Wampiry rewolucji (Drzazga Władimira Zazubrina) - Jastrzębska, Katarzyna (Przegląd Rusycystyczny, 2010)
THE VAMPIRES OF THE REVOLUTION (SLIVER VLADIMIR ZAZUBRIN) Summary The article presents the attempt to interpret the micro-novel Sliver (Щепка, 1923/1989) written by Vladimir Zazubrin (Vladimir Yakovlevich Zubtsov; 1895–1938).To the mind of the author, horror, atrocity and eeriness, that accompany the reading of Sliver result not only from the subject matter and problematique of the novel, but they are also, as the esthetic categories, the effect of visible references to the convention, developed by the classic horror novel. In Sliver we have to deal with the exploration and unconventional usage of the most im-portant motive of uncanny stories, which is the vampire motive. It served to Zazubrin, not only to reveal the chekist’s addiction to the “life-giving victim’s blood”, but also to show how much, sooner or later, the bolshevik idea of making the order presents its strangeness and deconstructive power in relation to mental construction of the intellectual, even when the revolution “seduces him” with the dictate of historical necessity. ВАМПИРЫ РЕВОЛЮЦИИ (ЩЕПКА ВЛАДИМИРА ЗАЗУБРИНА) Резюме Статья представлает собой попытку интерпретации повести Владимира Зазубрина (настоящая фамилия Зубцов; 1895–1938) под заглавием Щепка (1923/1989). Ощущение ужаса при чтении повести Зазубрина становится последствием не только самой тематики и проблематики произведения но и, заодно, использования писате-лем художественных приемов характерных для жанра готического романтического романа. По нашим представлениям, Зазубрин ссылается в Шепке на вампирический мотив — один из важнейших мотивов готической эстетики или, иначе говоря, жанра «хоррор». Благодаря этому приему, в повести подвергается разоблачению во-пeрвых, нужда (отнюдь не метафорическая) «ассенизаторов» революции в насилии и жесто-кости, которую может удовлетворить лишь только «жизнеобеспечивающая» кровь жертв, и, во-вторых, что жестокость, сопутствующая революции, рано или поздно, становится чуждой и враждебной психической конституции интеллигента. Даже тогда, когда революция «притягивает» его исторической необходимостью.